2022
DOI: 10.1111/vop.13018
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin reduces stress and does not affect ocular parameters in clinically normal cats

Abstract: Objective To describe the effects of gabapentin on ocular and behavioral parameters following oral administration in healthy cats. Materials and methods Masked, placebo‐controlled, randomized crossover‐design study. Ten young, healthy cats were scheduled for two veterinary visits 7 days apart and randomly assigned to receive a compounded capsule containing 100 mg of gabapentin or placebo (100 mg lactose powder) at the first visit and the opposite treatment at the second visit. Respiratory rate, heart rate, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Crowe et al 16 . demonstrated a significant reduction in stress scores and a significant increase in sedation scores following the administration of gabapentin in cats.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Crowe et al 16 . demonstrated a significant reduction in stress scores and a significant increase in sedation scores following the administration of gabapentin in cats.…”
Section: Discussionmentioning
confidence: 97%
“…Crowe et al 16 demonstrated a significant reduction in stress scores and a significant increase in sedation scores following the administration of gabapentin in cats. In the current study, although we did not collect sedation and/or stress scores in rabbits, it can be inferred that gabapentin administration resulted in easier handling and likely reduced stress levels in rabbits.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations